Increasing agricultural productivity & enhancing food security in Africa: Synopsis of the international conference held 1-3 November 2011 in Addis Ababa - Asenso-Okyere, Kwadwo; Jemaneh, Samson (International Food Policy Research Institute, 2012)
Increasing agricultural productivity in Africa calls for broader policy and strategic frameworks that encompass agro-industrial and agribusiness services along with farming. The agricultural system’s transformation will have the most impact when innovators have the explicit perspective that the green revolution and agro-industrial and agribusiness development must go hand-in-hand. This perspective will result in innovations that reduce poverty through broad-based economic growth, which includes enhanced food security, employment creation, and added value and wealth across the economy’s farming and nonfarming sectors.